2013
DOI: 10.1074/jbc.m112.410274
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Directly Induces p53-up-regulated Modulator of Apoptosis (PUMA) during the Rapid Induction of Apoptosis in Myc-driven B-cell Lymphomas

Abstract: Background: TGF-β induces apoptosis in Burkitt's lymphoma cells.Results: PUMA is a direct target gene of TGF-β signaling and is required for rapid apoptosis.Conclusion: TGF-β-mediated direct induction of PUMA contributes to apoptosis in human and murine c-Myc-driven lymphomas.Significance: These studies link TGF-β signaling and transcriptional activation of PUMA, two factors with critical roles in regulating B-cell survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…Although PUMA was identified as a target gene of p53, 31 the transcription of PUMA can be stimulated by other factors including p63, p73, NF-kB, FOXO, and SMAD4. 34, 35, 36, 37, 38 Previous studies have shown that cisplatin activates the Abl tyrosine kinase to stimulate p63 and p73. 9, 10, 11, 12 The wild-type level of PUMA α expression in some of the Abl +/+ ; p53 −/− kidneys could, therefore, be driven by the Abl-p63 or the Abl-p73 pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PUMA was identified as a target gene of p53, 31 the transcription of PUMA can be stimulated by other factors including p63, p73, NF-kB, FOXO, and SMAD4. 34, 35, 36, 37, 38 Previous studies have shown that cisplatin activates the Abl tyrosine kinase to stimulate p63 and p73. 9, 10, 11, 12 The wild-type level of PUMA α expression in some of the Abl +/+ ; p53 −/− kidneys could, therefore, be driven by the Abl-p63 or the Abl-p73 pathways.…”
Section: Resultsmentioning
confidence: 99%
“…The upregulation of PUMA α in the Abl +/+ ; p53 −/− mice is likely to be mediated by p63 and/or p73, as previous studies have established a redundant role of these three transcription factors in PUMA α expression. 34, 35, 36, 37, 38 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had established TGFβ1 as a potent inhibitor of hematopoiesis by its capability of inducing cell cycle arrest and apoptosis in early hematopoietic stem cells (Isufi et al 2007;Soderberg et al 2009). TGFβ1 has also been shown to induce apoptosis and cell cycle arrest in several hematopoietic malignant cells lineages by diverse mechanisms, such as upregulating the cyclin-dependent kinases (CDK) inhibitor p21 (Tvrdik et al 2006), apoptosis modulator, p53 up-regulated modulator of apoptosis (PUMA) (Spender et al 2013), proapoptotic mitochondrial protein Bax (Bakhshayesh et al 2012) and Myc antagonist Mad1 (Wu et al 2009) while down-regulating anti-apoptotic proteins, such as Bcl-2 and Bcl-xl (Bakhshayesh et al 2012), and pro-mitogenic transcription factor Myc (Wu et al 2009). The malignant hematopoietic cells employ several described mechanisms to evade cytostatic effects of TGFβ1, becoming able to grow and spread (Dong and Blobe 2006;Isufi et al 2007), highlighting the importance of TGFβ1 signalization in counteract malignant cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…This polymorphism was investigated in breast by Oda et al (2012) and oral cancer by Carneiro et al (2013) and by several others in diverse solid cancers, but has been poorly investigated in HM. In hematological scenario, TGFβ1 is shown to be a potent inhibitor of hematopoiesis (Soderberg et al 2009;Blank and Karlsson 2011), inducing cell cycle arrest and apoptosis in normal and even in some malignant hematopoietic cells lineages (Tvrdik et al 2006;Wu et al 2009;Bakhshayesh et al 2012;Spender et al 2013). Nevertheless, it has been demonstrated that many hematological cells employ mechanisms to circumvent cytostatic and apoptotic effects of TGFβ1 (Dong and Blobe 2006), and, in this case, this cytokine is responsible to promote a immunosuppressive environment by suppressing effector T H cells and inducing naïve T cells to differentiate into regulatory T cells (Tregs) (Yang et al 2013), similarly to that which occurs in some solid tumors (Massague 2008;Yang et al 2010;Kubiczkova et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While this protein is not mutated in BL, it may be subject to decreased expression through promoter methylation – even in tumors carrying mutant p5356 – suggesting that there are p53-independent regulators of PUMA active in BL. We recently showed that PUMA is a downstream effector of a transforming growth factor (TGF)-β-induced apoptosis pathway active in both human BL cell lines and murine Eμ-MYC -derived lymphoma cells 57. TGF-β also negatively regulates the BL survival factor, BCL-X L 58.…”
Section: Cooperating Mutationsmentioning
confidence: 99%